1997
DOI: 10.1149/1.1837660
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Study of the Gold Thiosulfate Reduction

Abstract: The electrochemical reduction of gold thiosulfate has been studied and compared to the reduction of gold cyanide. Gold thiosulfate is a potential replacement for gold cyanide in electro and electroless plating baths. Gold thiosulfate has a more positive reduction potential than gold cyanide and eliminates the use of cyanide. The standard heterogeneous rate constant, transfer coefficient, and diffusion coefficient for gold thiosulfate reduction were found to be 1.58 >< 1O cm/s, 0.23 and 7 x 10 cm2/s, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 9 publications
0
36
0
Order By: Relevance
“…Electrowinning is also an option for gold recovery, and [Au(S 2 O 3 ) 2 ] 3− anions in the pregnant solutions will migrate to the cathode, being reduced to metallic gold [64][65][66][67]. However, it is also not a feasible choice because undesirable reactions of other anions including copper (I) thiosulfate complexes, sulfur-oxygen anions and other metal thiosulfate complexes in the solutions can occur on the electrode surface.…”
Section: High Requirements On the Solution Ph Values Resin Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrowinning is also an option for gold recovery, and [Au(S 2 O 3 ) 2 ] 3− anions in the pregnant solutions will migrate to the cathode, being reduced to metallic gold [64][65][66][67]. However, it is also not a feasible choice because undesirable reactions of other anions including copper (I) thiosulfate complexes, sulfur-oxygen anions and other metal thiosulfate complexes in the solutions can occur on the electrode surface.…”
Section: High Requirements On the Solution Ph Values Resin Adsorptionmentioning
confidence: 99%
“…Ammonia-free thiosulfate leaching process by Barrick Gold Corporation to treat a carbonbearing sulfide gold ore pretreated with acidic or alkaline pressure oxidation [4,5]. [64][65][66][67] Low current efficiency and high energy consumption due to the undesirable reactions Difficulty in cyclic utilization of pregnant thiosulfate solutions…”
Section: Introductionmentioning
confidence: 99%
“…The hemispherical bulges/bubbles formation in the annealed gold film is related to the incorporation of impurities such as hydrogen gas in the as-deposited gold film which is reduced generally in parallel with metal deposition during the electrodeposition. In the literature, it is also reported that the gold cyanide complex ions are reduced at very high negative potentials which in turn resulting in the co-deposition of hydrogen ions [24]. Therefore, at this annealing temperature, hemispherical bulges/bubbles are formed due to the trapped hydrogen gas underneath the deposit, trying to evolve out from the deposit surface.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its electronic structure, S 2 O 3 2¹ has a stronger complex ability with heavy metals than sulfate and sulfite, such as Au 50 and Cu. [51][52][53] However, the interaction between S 2 O 3 2¹ with Co, Cr, Fe and Ni is still unknown.…”
Section: Discussionmentioning
confidence: 99%